AGE CHARACTERISTICS OF SCHOOL-AGED CHILDREN - Gofurov Abduvokhid Makhmudovich; Gofurov Abdushokir Makhmudovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article considers the basic concepts of physical preparation and technical preparation, physical preparation, the concept of individual development of the body is considered constant, natural changes in the size of the body, and functional characteristics of organs and systems.